The influence of the Youth Olympic Games on the well-being of youth athletes - Stålstrøm, Jannicke; Iskhakova, Marina; Andersson, Erik P. (Frontiers in Sports and Active Living, 2025)
IntroductionParticipating in sports is more than a competition; it is an avenue for personal growth and development, especially for young athletes. The Youth Olympic Games (YOG), established by the International Olympic Committee in 2010, is a unique platform for athletes aged 15–18 to showcase their skills while gaining invaluable life experiences. This study explores the influence of participation in the YOG, focusing on athletes' physical, mental, social, and emotional well-being. MethodsUsing a retrospective mixed-methods framework, 173 participants (47% female and 53% male) who competed in one of the four YOG events held between 2010 and 2016 were surveyed in 2017, followed by interviews 6 months later in 2018 with 30 of the participants. Quantitative data on 18 well-being items assessed on a 5-point Likert scale was analyzed with a one-sample Wilcoxon signed-rank test, and the interview data was analyzed using a top-down thematic approach. Results and discussionParticipants' responses were significantly above “neutral” (P < 0.001) on the 18 items about the YOG impact, suggesting a positive effect of the YOG across the four dimensions of well-being. The interviews complemented and informed the survey by providing deeper insights and context, to show that taking part in the YOG and its educational programs influence, and are important for the young elite athletes' psychometric development. Recognizing this impact, more attention should be given to developing tools and strategies to support the social and emotional well-being of youth elite athletes in sports. A better understanding of the impacts of participating in the YOG can foster a healthier, more informed generation of athletes and community members.